Marginal abatement cost of electricity generation from renewable energy in Thailand - Phitsinee Muangjai (2020)
© 2019 Electricity is very important for daily living and plays a major role in national development in Thailand with around 20.5% proportion in national final energy consumption, mainly from burning fossil fuels which have a direct effect to the greenhouse gas emission level of the country. Hence, the country has launched the Nationally Determined Contribution (NDC) Roadmap which covering on the 2021 to 2030 period and focused mainly on the energy, especially on power generation, and transport sector mitigation activities. This study has focused on the estimation of the marginal abatement cost (MAC) of electricity generation from renewable energy which consists of (i) natural type (solar energy, wind power, and hydro energy), and (ii) bioenergy type (biomass, biogas, and waste). As widely known, MAC is one of the most important tools for policy decision in prioritization in greenhouse gas emission reduction strategy which represents the importance and necessity of electricity production from each renewable energy type that affects the reduction of greenhouse gas (GHG) emissions of the country. We found that the marginal abatement cost (MAC), from various size and type, of natural type from -4,780.80 to 5,248.32 THB/tCO2eq and bioenergy type are from -4,913.28 to 134.29 THB/tCO2eq. The factors that affect to MAC of each renewable energy type are mixed results but the major factors are plant factor, investment cost, location, and size (in terms of economy of scale), respectively.